Business as Usual : A Collaborative and Inclusive Investigation of Existing Resources, Strengths, Gaps and Challenges to be Addressed for Sustainability in Teaching and Learning in Australian University Business Faculties : Final Report. - Freeman, Mark; Hancock, Phil; Simpson, Lyn; Sykes, Chris; Petocz, Peter; Densten, Iain; Gibson, Kathy (Carrick Institute for Learning and Teaching in Higher Education, 2008)
Final report from a scoping study that is a collaborative and inclusive investigation of existing resources, strengths, gaps and challenges to be addressed in order to secure sustainable, effective teaching and learning in business faculties at Australian universities. It was conducted by the Australian Business Deans Council Teaching and Learning Network, and the report provides an examination of the problems, issues and opportunities facing business education in Australia today. The action research investigation strategy included a literature review, and interviews and focus groups with representative stakeholders from academic, professional and industry associations as well as students and academic leaders that identified key issues of concern. These were then clustered into generic themes in an iterative collaborative process involving key stakeholders culminating in the development of three follow-on proposals: building professionally relevant learning and industry engagement in the business curriculum; building and assessing the development of generic skills across the business curriculum; and valuing quality teaching in business education. It was recommended that the Australian Business Deans Council and Teaching and Learning Network form a national reference group to support sustainable industry engagement and to assist in maintaining the relevance and excellence of contemporary business education.